Hubungan Aktivitas Fisik dengan Kejadian Hipertensi pada Usia Produktif di Puskesmas Sidomulyo Rawat Inap Kota Pekanbaru - Yessi Rahayu; Abdul Karim; Goldha Farouliu Peadutu (Jurnal Kesehatan Amanah, 2024)
One of the factors influencing hypertension is physical activity. The highest prevalence of hypertension is found in individuals who tend to have low levels of physical activity (49.8%). Objective: To determine the correlation between physical activity and the incidence of hypertension in the working-age population at Puskesmas Sidomulyo Rawat Inap, Pekanbaru. Methods: This study is an analytic observational study with a cross-sectional approach and accidental sampling technique. Data analysis was conducted using the Chi-square test. Findings: There is a significant correlation between physical activity and the incidence of hypertension in the working-age population at Puskesmas Sidomulyo Rawat Inap, Pekanbaru, with a p-value of 0.000. Implications: A significant correlation was found between physical activity and the incidence of hypertension in the working-age population at Puskesmas Sidomulyo Rawat Inap, Pekanbaru.